1979
DOI: 10.1149/1.2129098
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Operation of a Thin‐Film SnO x Conductance‐Modulation Carbon Monoxide Sensor

Abstract: ANODIC OXIDE FILMS 627 some affinity to the effects of chloride on silicon oxidation (11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 370 publications
(116 citation statements)
references
References 10 publications
4
109
0
3
Order By: Relevance
“…, and O − is believed to be dominant [34]), and thus SnO 2 will show a high resistance. When ethanol is introduced at moderate temperature, SnO 2 is exposed to the traces of reductive gas.…”
Section: Resultsmentioning
confidence: 99%
“…, and O − is believed to be dominant [34]), and thus SnO 2 will show a high resistance. When ethanol is introduced at moderate temperature, SnO 2 is exposed to the traces of reductive gas.…”
Section: Resultsmentioning
confidence: 99%
“…[17,18] Although the value of the exponent applied to the concentration is commonly attributed directly to the different oxygen species at the sensor surface that are proposed to mediate the sensor response recent work has shown that it may, in fact, be due to microstructure. [10,19] The sensing results for the 5 minute deposition (5400 nm-thick) are discussed below.…”
Section: Figure 11:-response Vs [Ethanol]mentioning
confidence: 99%
“…Structure and gas sensing properties of nanowire sensors 3.1 SnO 2 nanowires formed by vapor transport SnO 2 is the gas sensing material that has been most extensively studied (Windischmann & Mark, 1979;Heiland, 1982;Tamaki et al, 1989). SnO 2 nanowires have also recently been studied vigorously as a gas sensing material (Ramirez et al, 2007;Kumar et al, 2009).…”
Section: Evaporation In Ambient Airmentioning
confidence: 99%